Changes in implementation of personal protective measures by ordinary Japanese citizens: A longitudinal study from the early phase to the community transmission phase of the COVID-19 outbreak. (July 2020) - Machida, Masaki; Nakamura, Itaru; Saito, Reiko; Nakaya, Tomoki; Hanibuchi, Tomoya; Takamiya, Tomoko; Odagiri, Yuko; Fukushima, Noritoshi; Kikuchi, Hiroyuki; Amagasa, Shiho; Kojima, Takako; Watanabe, Hidehiro; et al.
Graphical abstract: Highlights: Improvement in personal protective measures since early phase of COVID-19 outbreak. The prevalence of avoiding touching the eyes, nose, and mouth is still low. Fewer men and fewer low-income households have altered their behavior. Self-isolation seems difficult for people with low income levels. There remains room for improvement in personal protective measures by citizens. Abstract: Objectives: To clarify changes in the implementation of personal protective measures among ordinary Japanese citizens from the early phase of the COVID-19 outbreak to the community transmission phase. Methods: This longitudinal, internet-based survey included 2141 people (50.8% men; 20–79 years). The baseline and follow-up surveys were conducted from February 25–27, 2020, and April 1–6, 2020, respectively. Participants were asked how often they implemented the five personal protective measures recommended by the World Health Organization (hand hygiene, social distancing, avoiding touching the eyes, nose and mouth, respiratory etiquette, and self-isolation) in the baseline and follow-up surveys. Results: Three of the five personal protective measures' availability significantly improved during the community transmission phase compared to the early phase. Social distancing measures showed significant improvement, from 67.4% to 82.2%. However, the prevalence of avoiding touching the eyes, nose, and mouth, which had the lowest prevalence in the early phase, showed no significant improvement (approximately 60%). Multivariate logistic regression analysis revealed that men and persons of low-income households made fewer improvements than women and persons of high-income households. Conclusions: The availability of personal protective measures by ordinary citizens is improving; however, there is potential for improvement, especially concerning avoiding touching eyes, nose, and mouth.